Editorial Commentary: Stop digging: regenerating science for an inclusive and sustainable future - Kazembe, Lawrence; Kangira, Jairos (Namibian Journal for Research, Science and Technology, 2022)
Healey’s first law of holes is, "if you find yourself in a hole, stop digging". Over the years others have added to that law. The second law say "if there is any open hole fill it" - and third law says "any hole not filled now will cause more damage in the future". The first law is attributed to a British politician Healey- following an interview with the Statesman magazine in 1986. Thus, others have referred to it as "Healey’s first law of politics" (Guardian, 2015). Although popularized by Healey, the first recorded use of this saying dates back to 1911, where the Washington Post published the original saying on the sixth page. This saying reads: nor would a wise man, seeing that he was in a hole, go to work and blindly dig it deeper. The First Law of Holes simply mean "know when to stop". There are many societal lessons we can learn from this concept of stop digging. You may find this law relevant to your business, your political beliefs, or even your financial situation. But the message remains all the same; if you find you are in trouble, it’s best to quit whatever it is you are doing that has gotten you to this point. But first, recognize the hole you have dug. That is to say, the first step in finding a solution is admitting there is a problem. It might take a lot of pride-swallowing, but it is worth it, to be honest about what you are struggling with. To rise above your challenges, you can’t continue to go downward. There are usually many factors at play when it comes to finding a solution. The holes adage speaks to the society we live in. It has been littered with too many "may-tries", a great many experiments to the detriment of the economy, and people around. Tragically, citizens are often taken as pawn. In the 1980s - following the oil crisis - developing countries were faced with the need for structural reforms of their economies - which drove the privatization programme. While the idea was meant to promote efficiency, countries eventually were found in a hole. Each dug a hole. Many state-owned companies were sold, leading to massive unemployment and deepened poverty. The working class was sacrificed. However, the best thing to do was to realize that they (countries) were in a hole, and then stop digging. The first step was to stop doing harm. Stop approving any more expenses and assess the situation at hand. This was never done. Following at the heals of structural adjustments was outsourcing, which further shed more jobs. More also it led to a culture of profit making, and ballooned costs - again to the detriment and neglect of delivery of social services for the benefit of the citizenry. This leads to lessons of the second and third laws of holes. The existing holes were left open and are causing societal damages. Of course, the history of outsourcing dates back to the time of the Industrial Revolution, which began in Europe in 1750s. The Industrial Revolution led to the mass production of goods and caused the growth of markets and profits. Many companies experienced a shortage of local human resources, so they started contracting with third-party firms to delegate the accounting, legal, and insurance tasks. Outsourcing is based on the economic principle of "opportunity cost". Outsourcing was not formally identified as a business strategy until 1989 (Kim, 2018; Gonzales et al. 2020). However, most organizations were not totally self-sufficient; they outsourced those functions for which they had no competency internally. One of the best examples of outsourcing, outstaffing, and recruiting is Japan during the reign of Meiji. The period that marked a place for itself in the history books as the Meiji Restoration, became a major reason for Japan’s industrial rise later in the 1900’s. Outsourcing is the buzz word of the new millennium – while companies are increasingly moving jobs offshore to cut down costs, the public is feeling cheated that their jobs are being “stolen” by cheap, foreign labour.